A probability approach to pharmaceutical demand and price setting: Does the identity of the third-party payer matters for prescribing doctors? - Dag Morten Dalen; Marilena Locatelli; Enrico Sorisio; Steinar Strøm (Center for Economic Studies and ifo Institute (CESifo), 2011)
TNF-alpha inhibitors represent one of the most important areas of biopharmaceuticals by sales, with three blockbusters accounting for 8 per cent of total pharmaceutical sale in Norway. Novelty of the paper is to examine, with the use of a unique natural policy experiment in Norway, to what extent the price responsiveness of prescription choices is affected when the identity of the third-party payer changes. The three dominating drugs in this market, Enbrel, Remicade, and Humira, are substitutes, but have had different and varying funding schemes - hospitals and the national insurance plan. A stochastic structural model for the three drugs, covering demand and price setting, is estimated in a joint maximum likelihood approach. We find that doctors are more responsive when the costs are covered by the hospitals compared to when costs are covered by national insurance.
Keywords: C35; D43; I18; L11; 330; pharmaceuticals; discrete choice model; funding-schemes